Transport Policy of the European Union: Between Strategic Goals and Economic Reality - E. A. Sergeev (Международная аналитика, 2025)
The transport sector is one of the cornerstones of the European Union’s single internal market. While it allows to logistically connect the countries of the integration union, it also represents challanges, especially climate ones, as transportation is responsible for a significant share of greenhouse gas emissions. Due to the growing significance of this particular sector of the economy, it is becoming increasingly important to analyze and compare regulatory practices adopted at both supranational and national levels. The purpose of this research is to assess the current components of the EU transport policy objectives and to relate them to the reality of the individual elements of the EU transport sector. The article highlights the inconsistencies inherent in the implementation of transport policy due to the mismatch between its goals and capabilities. To a certain extent, this premise makes it difficult to apply the concept of Europeanization to transport policy, which regulates an economic phenomenon that is unique in its internal characteristics. The paper describes the key elements of the EU transport policy, emphasizing its extensive and differentiated nature. Nevertheless, it can hardly be said that there have been significant changes in its goal-setting during evolution. Thus, the policy fits into the following logical construction: its development depends on the depth of the EU integration on the one hand, and is constrained by inherent imbalances on the other. It is these imbalances that are currently preventing the achievement of emission reduction and modal shift targets.The development of transport infrastructure and the stimulation of investment in this area are also problematic. The ambiguous nature of the effectiveness of the European Union’s transport policy is emphasized due to the above-mentioned controversies in this area. Such results determine the directions of future measures influencing the transport sphere in the EU, taking into account the fundamental inability to resolve the contradiction consisting in the connection between economic growth and the increase in harmful emissions into the atmosphere.